(untitled) (Research, Society and Development, 2022)
Idiopathic thrombocytopenic purpura (ITP) is an autoimmune disease characterized by a low number of platelets, the cells that play a role in the blood clotting process, and affects mainly people between the ages of 18 and 24 and is manifested through minor bleeding and purple spots on the skin. This study aims to help expand readers’ knowledge by focusing on the diagnosis of ITP based on the compilation of bibliographic materials acquired through searches on the Scientific Electronic Lirary Online platforms - SCIELO, Google Scholar, Ministry of Health (MS), Virtual Library in Health, which after going through exclusion and inclusion criteria, resulted in 25 citations, among articles and protocols. The results obtained show that in cases of suspected ITP, the diagnosis is made by exclusion process, after performing the anamsis, complete blood count and smear and confirming the presence of thrombocytopenia, tests will be performed to exclude other diseases that also cause thrombocytopenia noting the absence of other clinical conditions, the diagnosis of ITP will be confirmed.